2011
DOI: 10.5964/ijpr.v5i2.65
|View full text |Cite
|
Sign up to set email alerts
|

The Exploration of the Relationship between Participation in Organized Activity and Cross-Group Friendships

Abstract: Cross-group friendship is an important element in regard to reducing prejudice and increasing positive interracial interactions among young adults. In order to facilitate the formation of cross-group friendships, organized activity participation (e.g., community service and school-based extracurricular activities) may provide an environment that supports positive cross-cultural interactions and contacts. The sample used for this study consisted of 601 college students. We tested whether participation in an org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Researchers have emphasized the value of intergroup contact through leisure activities for immigrants’ acculturation (Kim, 2012 ; Suh & Kim, 2011 ). These authors found that by interacting with other ethnic groups through leisure activities, immigrants established and developed a sense of friendship and gained cultural knowledge, which improved cultural and ethnic understandings.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have emphasized the value of intergroup contact through leisure activities for immigrants’ acculturation (Kim, 2012 ; Suh & Kim, 2011 ). These authors found that by interacting with other ethnic groups through leisure activities, immigrants established and developed a sense of friendship and gained cultural knowledge, which improved cultural and ethnic understandings.…”
Section: Discussionmentioning
confidence: 99%
“…Because of cultural identity and pride, Kim et al ( 2014 ) also found that participation in activities with in-group members served as a motivator for leisure participation. However, other studies have emphasized the value of leisure engagement with other ethnic groups (i.e., out-groups) to facilitate acculturation, as well as improved cultural and ethnic understanding among immigrants (Kim, 2012 ; Suh & Kim, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggested the idea that leisure may provide a context to which to foster positive intergroup contacts and interactions (Cameron, Rutland, Brown, & Douch, 2006; Edginton, Jordan, DeGraaf, & Edginton, 1995). For example, using a sample of college students, Suh and Kim (2011) explored the relationship between organized activities (e.g., community-based activities and school-based extracurricular activities) and cross-group friendships. This study suggests that organized activities provided an environment that supports positive cross-cultural interactions and contacts.…”
Section: Introductionmentioning
confidence: 99%